PENINGKATAN KETERAMPILAN MEMBACA PEMAHAMAN DENGAN MENGGUNAKAN STRATEGI (QAR) QUESTION ANSWER RELATIONSHIP PADA SISWA DI SEKOLAH DASAR - Rapida Yana; Yusnira Yusnira; Iis Aprinawati (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2023)
This research is conducted due to the low achievement of students reading comprehension skill on children's story material of grade IV SDN 012 Langgini On of the solusion to evercome the problem by implementing QAR Question Answer Relationship Strategy. This study aims at improving students readning comprehension skill achievement on child story material through the impelementation of QAR Question Answer Relationship Strategy on grade V SDN 012 Langgini. This is a classroom action research with two child each cycle consists of two meetings and four stages namely planning, implementing. Observing and reflecting. The subject of this research is grade IV students, total 17 students, 10 male students and 7 famale students. The data collection teachique employed are documentation, observasion, and tes. Based on the results of data analysis, it can be seen that there is an increase in the results of students reading comprehension skill on texs story material before the action, the average completeness of the reading comprehension results is 60. Then in the first cycle of the first meeting increased to 62,35 the first cycle of the second meeting increased to 79,75. Then cycle II meeting I increased become 77,94 and cycle II meeting II increased become 81,47. It can be inferred concluded that the application of the QAR Strategy can improve students reading comprehension skills on the child story material for grade VSDN 012 Langgini.